RELASI ANTARMANUSIA DALAM NILAI-NILAI BUDAYA BUGIS: PERSPEKTIF FILSAFAT DIALOGIS MARTIN BUBER - Hadis Badewi, Muhammad (Jurnal Filsafat "WISDOM", 2015)
This article analyzes the local wisdom of Bugisnese that guide the relationship among human which is highlighted in the Bugis ancient book, La Galigo. This article aims to explain concepts of the human relationship in the cultural values of Bugisnese and its relevance to the human rights development in Indonesia. Using Martin Buber's philosophical perspective, this article adopts three types of relationship known as I-It, I-Thou and I-Eternal Thou. In Bugisnese context, Buber's perspectives have been adopted and understood into the cultural concept/values for a long time. They practiced sipakasiri' which highlights a taboo relationship. They believed in sipassiriki as an ideal concept in human being relationship and contended that mappesona ri dewata seuwwae is the most crucial concept that exist among them. These shared Bugisnese values are relevant to the development of human rights in Indonesia.